Exotica searches at 13 TeV by CMS - Kirsanov Mikhail (EPJ Web of Conferences, 2016)
Results from searches for exotica signals in proton-proton collisions at √s = 13 TeV in the CMS detector at the LHC are presented. The analysed data are collected during the first year of the LHC Run II in 2015 and correspond to integrated luminosities from 2.2 to 3.3 fb−1.